ANALYSIS OF THE COMPARATION OF THE INCOME OF THE BIG CHILI AGROINDUSTRY AND THE SMALL CHILI AGROINDUSTRY IN SUSUKAN DISTRICT SEMARANG REGENCY - Fikri Haikal Hidayat (Universitas Wahid Hasyim, 2023)
The aim of this research was to analyze and compare the total of the production cost, income and profitability of the big chili agroindustry with the small chili agroindustry. This research was held in December 2022 in Susukan District, Semarang Regency. This research used survey as the method. The sampling method was proportional random sampling. The total of the population was 120 respondents, whereas using Slovin method, the sample was determined as 90 respondents, consisting 60 big chili farmers and 30 small chili farmers. The agroindustry cost analysis, revenue, income and profitability data analysis method was quantitative. Meanwhile, the statistical tests for differences were the independent sample t-test, Mann Whitney U Test and one sample t-test, which were processed using SPSS software. The result of this research showed that the total production cost, revenue, income and profitability of the big chili agroindustry were Rp. 11.946.719; Rp. 60.473.683; Rp. 48.526.964 and 4,09%, with the average land area of 2.571/m^2/planting period. Whereas, the same data of the small chili agroindustry being Rp. 8.027.116; Rp. 24.191.967; Rp. 16.164.850 and 2,06%, with the average land area of 1.6967/m^2/planting period. The Mann-Whitey U Test showed the differences in revenue, income and profitability of the big chili agroindustry. One sample t-test showed that the profitability of the big chili agroindustry was 4,09%, higher than the 2022 BRI deposit rate, which was 2,75%, thus concluded as profitable. Whereas, the profitability of the small chili agroindusty of 2,06% was lower than the deposit rate of 2,75%, thus concluded as non-profitable.